Nutritional status and mortality of refugee and resident children in a non-camp setting during conflict: follow up study in Guinea-Bissau - Aaby, Peter (British Medical Journal, 1999)
OBJECTIVE: To study the effects on children of humanitarian aid agencies restricting help to refugee families (internally displaced people). DESIGN: Follow up study of 3 months. SETTING: Prabis peninsular outside Bissau, the capital of Guinea-Bissau, which has functioned as a refugee area for internally displaced people in the ongoing war, and the study area of the Bandim health project in Bissau. PARTICIPANTS: 422 children aged 9-23 months in 30 clusters. MAIN OUTCOME MEASURES: Mid-upper arm circumference and survival in relation to residence status. RESULTS: During the refugee situation all children deteriorated nutritionally, and mortality was high (3.0% in a 6 week period). Rice consumption was higher in families resident in Prabis than in refugees from Bissau but there was no difference in food expenditure. Nutritional status, measured by mid- upper arm circumference, was not associated with rice consumption levels in the family, and the decline in circumference was significantly worse for resident than for refugee children; the mid-upper arm circumference of refugee children increased faster than that of resident children. For resident children, mortality was 4.5 times higher (95% confidence interval 1.1 to 30.0) than for refugee children. Mortality for both resident and refugee children was 7.2 times higher (1.3 to 133.9) during the refugee’s stay in Prabis compared with the period after the departure of the refugees. CONCLUSION: In a non-camp setting, residents may be more malnourished and have higher mortality than refugees. Major improvements in nutritional status and a reduction in mortality occurred in resident and refugee children as soon as refugees returned home despite the fact that there was no improvement in food availability.